2018
DOI: 10.1093/jas/sky151
|View full text |Cite
|
Sign up to set email alerts
|

Sex bias of the birth litter affects surge but not tonic LH secretion in gilts1

Abstract: The physiology and behavior of gilts that develop in a male-biased litter can differ from gilts that develop in a female-biased litter. We hypothesized that gilts from male-biased litters will have a delayed and attenuated luteinizing hormone (LH) surge, and reduced LH pulse frequency and amplitude compared to gilts from female-biased litters. Gilts were selected at birth from male-biased (>60% males n = 10) or female-biased (>60% females n = 9) litters. From 18 wk of age, detection of puberty using daily boar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…Previous studies in both mice and pigs have demonstrated effects of intrauterine proximity to male foetuses on foetal growth and morphology [40][41][42][43][44]. Additionally, it is known that sex ratio of a litter has consequences for both gilt and boar postnatal reproductive performance [45][46][47][48][49][50][51][52]. Collectively, given the propensity for sex-biased litters and the strong links between sex of other foetuses within a litter and postnatal success, critical interrogation of the association between vitamin D status and conceptus development in sex biased litters may provide important insights to improve pig production systems.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies in both mice and pigs have demonstrated effects of intrauterine proximity to male foetuses on foetal growth and morphology [40][41][42][43][44]. Additionally, it is known that sex ratio of a litter has consequences for both gilt and boar postnatal reproductive performance [45][46][47][48][49][50][51][52]. Collectively, given the propensity for sex-biased litters and the strong links between sex of other foetuses within a litter and postnatal success, critical interrogation of the association between vitamin D status and conceptus development in sex biased litters may provide important insights to improve pig production systems.…”
Section: Discussionmentioning
confidence: 99%
“…In the commercial pig a sex-biased in utero environment hormonal environment has been shown to affect several aspects of reproductive function in the offspring. Specifically, females that originate from male-biased litters have fewer teats [8], a lower conception rate at first mating [9], increased sensitivity to gonadotropins [10], and altered LH surge profiles [2], compared to offspring originating from female-biased litters. The cause of these changes in reproductive efficacy remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…The Developmental Origins of Health and Disease (DOHaD) describes how the developmental plasticity and in-utero programming of offspring could contribute to susceptibility of a range of adult disease with the maternal intra-uterine hormonal environment has been shown to influence many aspects of offspring development, some of which are sexually dimorphic in nature [1]. Studies specifically investigating the influence of foetal hormones have indicated effects such as endocrine alterations [2], altered physiological development such as delayed lung maturation [3], behavioural changes such as increased aggression [4], and reduced maternal and paternal behaviour [5]. These effects are observed following an androgenisation of the uterine environment in litter bearing species, often caused by disproportionate numbers of males in-utero .…”
Section: Introductionmentioning
confidence: 99%
“…The maternal intrauterine hormonal environment has been shown to influence many aspects of offspring development, some of which are sexually dimorphic in nature [ 1 ]. Studies specifically investigating the influence of fetal hormones have indicated effects such as endocrine alterations [ 2 ], altered physiological development [ 3 ], and behavioral changes [ 4 , 5 ]. These effects are observed in litter bearing species following an androgenization of the uterine environment, often caused by disproportionate numbers of males in utero.…”
Section: Introductionmentioning
confidence: 99%
“…In the commercial pig, a sex biased in utero environment has been shown to affect several aspects of reproductive function in the offspring. Specifically, females that originate from male-biased litters have fewer teats [ 8 ], a lower conception rate at first mating [ 9 ], increased sensitivity to gonadotropins [ 10 ], and altered lutenizing hormone (LH) surge profiles [ 2 ], compared to offspring originating from female-biased litters. The cause of these changes in reproductive efficacy remains unclear.…”
Section: Introductionmentioning
confidence: 99%